2009
DOI: 10.1089/ars.2008.2291
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic and Kinetic Details of Catalysis of Thiol-Disulfide Exchange by Glutaredoxins and Potential Mechanisms of Regulation

Abstract: Glutaredoxins are small, heat-stable proteins that exhibit a characteristic thioredoxin fold and a CXXC=S activesite motif. A variety of glutathione (GSH)-dependent catalytic activities have been attributed to the glutaredoxins, including reduction of ribonucleotide reductase, arsenate, and dehydroascorbate; assembly of iron sulfur cluster complexes; and protein glutathionylation and deglutathionylation. Catalysis of reversible protein glutathionylation by glutaredoxins has been implicated in regulation of red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
217
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(231 citation statements)
references
References 143 publications
(249 reference statements)
14
217
0
Order By: Relevance
“…Despite its important roles, mechanisms regulating cellular activity of Grx1 are poorly understood. It has been proposed that association of Grx1 with scaffolding proteins (eg, caveolae in membrane lipid rafts) may regulate Grx1 function, as the activity of the enzyme is thought to occur via an encounter reaction 26. Consistent with this proposal, we show that Grx1 co‐immunoprecipitates with eNOS in rabbit aorta.…”
Section: Discussionsupporting
confidence: 87%
“…Despite its important roles, mechanisms regulating cellular activity of Grx1 are poorly understood. It has been proposed that association of Grx1 with scaffolding proteins (eg, caveolae in membrane lipid rafts) may regulate Grx1 function, as the activity of the enzyme is thought to occur via an encounter reaction 26. Consistent with this proposal, we show that Grx1 co‐immunoprecipitates with eNOS in rabbit aorta.…”
Section: Discussionsupporting
confidence: 87%
“…1a). Glutathionylation of proteins has been shown to be mediated by GRx, a thiol-rich enzyme involved in antioxidative defense (34). Incubation of UCP3 with GRx1 and GSH prior to BioGEE treatment and pull-down with streptavidin significantly diminished the recovery of UCP3 (Fig.…”
Section: Ucp3mentioning
confidence: 93%
“…On the basis of the recent evidence of Menon and Board [6] on the GSTO1-1 role in glutathionylation cycle, we speculated that enhanced deglutathionylase activity of GSTO1 might contribute to the process of deglutathionylation, resulting in decreased total S-glutathionylation level in TCC tumor tissue. Until now, the regulatory role of deglutathionylation (reduction of PrSSG) in redox signal transduction was investigated concerning mainly glutaredoxins as the major intracellular deglutathionylating enzymes in the cells [16]. Moreover, it has been shown that manipulation of glutaredoxin levels affects downstream signaling events by changing the protein glutathionylation status of the cells [16].…”
Section: Discussionmentioning
confidence: 99%